Looking At A New Strategy to Save the Sacramento – San Joaquin Delta - Fredenburg, Julia; Fredenburg, Robert (Consilience, 2012)
Water supply, flood control, and environmental management are fundamental challenges for the western United States. California’s unique development patterns, with nearly 20 million of its residents living in water starved southern California, has resulted in a system of water transfers and aqueduct systems that rely on water being pumped, collected and transferred from Northern California through an extensive and damaging pumping and aqueduct system. The Sacramento – San Joaquin Delta (the Delta) is the heart of California’s water source and the center of the transfer system. The Delta is an 837,594 acres area where the Sacramento and San Joaquin River join before entering the San Francisco Bay and then the Pacific Ocean. Water is pumped from the Delta through a system of aqueducts to agricultural users in the San Joaquin Valley and urban centers of the San Francisco Bay, Los Angeles and other communities throughout southern California. Unsustainable pumping of vast amounts of water yearly from the Delta has caused the collapse of several fish populations and has forced a rethinking of the federal and state water policies. United States federal and state river and water policies for the past 150 years have relied on maximizing conversions of wetlands for agricultural uses while placing a high priority on flood control on major rivers like the Mississippi, Missouri and Sacramento. As we move well into the 21st century the historic water policies of flood control and water exports have left the Delta facing an imminent collapse that threatens the massive California water transfers and the delta fisheries if immediate action is not taken. The effect of the collapse is potentially the loss of water to the 20 million California residences and the agricultural economy of the California San Joaquin Valley. Fortunately, the Delta provides a new laboratory for water policies and improved habitat and water quality while addressing the need for flood control. Images of the Delta will help to illustrate the multiplicity of interests that form the heart of the debate over California’s water future.